Tourism Education and Training for the Entrepreneurship Development - Paudyal, Narayan Prasad (The Third Pole: Journal of Geography Education, 2019)
This paper explores emerging concepts of tourism education, training and entrepreneurship development. Nowadays, the discourses on this theme have been growing in both developed and developing countries, especially for reducing unemployment rates through the education of youth people. For this purpose, this paper used secondary sources of data to analyze individual rationality and creativity of educated youth people for the entrepreneurship development in business sector. The analytical framework begins from the examination of tourism industry and processes for empowering those people since tourism industry is considered as one of the agents of socio-economic changes in developing countries, like Nepal. But it needs skilled and trained manpower to operate properly. The main theme of this paper is that the aforesaid manpower can be developed with entrepreneurship skills by providing education and training regarding this business. This paper entirely agrees that once the tourism industry is well run by removing hurdles seen in this sector, it can help increase employment opportunities, increase the country's revenue and solve many other social problems.